2016
DOI: 10.21475/ajcs.2016.10.03.p7306
|View full text |Cite
|
Sign up to set email alerts
|

Soil chemical properties, growth and production of sunflower under fertilization with biochar and NPK

Abstract: The use of biomass can contribute to improve the soil properties. The objective of this study was to evaluate the effect of fertilization with poultry litter biochar in combination with mineral fertilizer on soil chemical attributes, growth and yield components of sunflower. For this purpose, a greenhouse experiment was carried out in pots with a capacity of 20 dm 3 under randomized design, with treatments arranged in a factorial 5 × 4 design with four replicates. The treatments consisted of five doses of mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Researchers studying Chrysanthemum coronarium L., Calathea insignis, Solanum lycopersicum L., and Tagetes erecta L. have shown positive effects of biochar in rates ranging from 3-20%, which is less than our two highest rates [9,44,45]. Alternatively, studies conducted by Furtado et al [29] found that plant height was reduced in sunflower (Helianthus annus L.) when poultry biochar rate was increased beyond 5%, and Rajkovich et al [46] found that the growth of corn was reduced when food waste biochar rate was increased to 7%. This discrepancy between research findings, as highlighted by our experiments, implies that there appear to be multiple factors affecting the interaction between biochar and plant growth.…”
Section: Impacts Of Biochar On Plant Growthcontrasting
confidence: 57%
See 1 more Smart Citation
“…Researchers studying Chrysanthemum coronarium L., Calathea insignis, Solanum lycopersicum L., and Tagetes erecta L. have shown positive effects of biochar in rates ranging from 3-20%, which is less than our two highest rates [9,44,45]. Alternatively, studies conducted by Furtado et al [29] found that plant height was reduced in sunflower (Helianthus annus L.) when poultry biochar rate was increased beyond 5%, and Rajkovich et al [46] found that the growth of corn was reduced when food waste biochar rate was increased to 7%. This discrepancy between research findings, as highlighted by our experiments, implies that there appear to be multiple factors affecting the interaction between biochar and plant growth.…”
Section: Impacts Of Biochar On Plant Growthcontrasting
confidence: 57%
“…For example, Schmidt et al [28] found that the application of larger amounts of wood biochar did not have any significant effect on plant growth parameters of grapevines. In another study by Furtado et al [29], poultry biochar reduced the growth of sunflowers. These conflicting results illustrate that research must be tailored to specific crops and rates of application to determine the overall impacts on plant production.…”
Section: Introductionmentioning
confidence: 91%
“…Variable effects of biochar on seed emergence and plant growth have frequently been reported, which is largely related to the feedstock type, pyrolysis temperature, application rate, plant species, and soil type (Semida et al 2019;Furtado et al 2016;Kwapinski et al 2010;Chan et al 2008;Yamato et al 2006). Under salinity conditions, biochar can improve plant growth via different mechanisms; either directly by supplying nutrients and reducing Na + availability by surface adsorption or entrapment in the pores of biochar, or indirectly by increasing water availability and enhancing several soil physical, chemical, and biological properties (Yu et al 2019;Dahlawi et al 2018;Palansooriya et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Kavitha et al (2018) found that Depending on the crop and the type of biochar, biochar has been found to have both favourable and unfavourable impacts on plant development and yield. In addition, in another study by Furtado et al (2016) found that, biochar reduced the growth of sunflowers.…”
Section: Total N Available P and Available K Contents In Soilmentioning
confidence: 92%